(untitled) (Research, Society and Development, 2020)
The identification of nutritional deficiencies is an important tool to assist the management of fertilization in different cultures, as it makes it possible to diagnose in the field and thus direct actions to prove and correct the deficiency of some nutrient. Thus, this work aimed to evaluate the levels and accumulations of macro and micronutrients under nutritional deficiencies. An experiment was carried out in a DIC design, with three replications and twelve experimental plots. The dry matter yields, the contents and nutritional accumulations of the aerial part of Italian pumpkin under different omissions presented different statistics among themselves. The levels of macronutrients found in the sand part of Italian pumpkin and in the plants of the complete treatment are (g kg-1): P 4.87, K 24.20; Ca 39.54; Mg 5.05 and S 4.13. The levels of micronutrients found in the Italian pumpkin shoot of the complete treatment are (mg kg-1): Cu 7.71; Fe 182.27; Mn 418.59 and Zn 70.31. The omission of nutrients in Italian pumpkin causes nutritional imbalance in the plants.